Towards a new understanding of mineral tenure security : the demise of the property-law paradigm - Van Niekerk, Heleen (Department of Private Law, 2016)
South Africa's rich mineral endowment makes it a geologically favourable country for investment in its mining industry. However, even countries with geologically favourable conditions will not attract investment in its mining sector if the regulatory regime does not provide certainty and stability. One aspect of such a regulatory regime is the provision of mineral tenure security. Studies indicate that strong mineral tenure security is an important factor that investors take into account before investing is a country's mining industry. For example a study by J.M Otto found that out of a possible sixty factors influencing investment decisions, security of tenure was ranked second during the exploration phase and first during the mining phase. Conceptually, mineral tenure security defies a single definition. The concept requires certainty and stability of rights through the entire mining sequence with the aim of providing the best opportunity for right holders and investors to develop mines profitably and to maximise returns on investments. In this sense, mineral tenure security requires minimisation of risks and uncertainties that may prevent profitable development of mines and maximising returns on investments. The specific requirements for strong mineral tenure security depends on the theoretical underpinnings of the regulatory regime. This thesis argues that it is likely that in regimes with a strong private-law character, private-law rules will be significant for providing mineral tenure security. Conversely, in regimes with a strong public-law character, it is likely that private-law rules will not be central to the provision of mineral tenure security. In regimes with a strong public-law character, rules of administrative law, for example, are more likely to be significant for providing mineral tenure security. The Mineral and Petroleum Resources Development Act (MPRDA) came into operation in 2002. This thesis demonstrates that the Act brought about significant changes to the theoretical landscape of mineral law. Before the MPRDA, the regime pertaining to minerals was based on a combination of private holding and public administration of rights to minerals. The Act changed this landscape to one that is based predominantly in public law. Against this background, this thesis follows two courses of inquiry; the first with a mainly theoretical character and the second with a mainly practical character. The first (theoretical) course of inquiry investigates whether the private-law concepts that are traditionally associated with mineral tenure security, namely ownership of minerals and mineral resources and real rights in property, continue to strengthen mineral tenure security in the current regulatory regime. This course of inquiry also investigates the limitation of a private-law based approach to mineral tenure security. The second (practical) course of inquiry investigates how the current predominantly administrative regime strengthens mineral tenure security. The second course of inquiry attempts to identify the shortcomings of the current regulatory regime in strengthening mineral tenure security and also attempts to provide a set of solutions for these shortcomings.